Kualitas Udara Emisi Karbon Monoksida (Co) dan Persepsi Gangguan Kesehatan di Kota Tomohon: Prespektif Ekologis dan Kesehatan Lingkungan - Pangerapan, Sinthia Brigyta; Warlina, Lina; Hamzah, A. Hadian Pratama (LPPM Institut Pendidikan Nusantara Global, 2025)
Air pollution in urban areas is a serious problem, especially in locations with heavy traffic and incomplete combustion activities. This study aims to analyse air quality, specifically the concentration of Carbon Monoxide (CO), on Jalan Pusat Kota Tomohon and to identify the perception of the public and satay vendors regarding the health problems they may experience. This descriptive study uses direct measurement methods at three strategic locations and the distribution of questionnaires to respondents. The results show that the average CO level on Jalan Pusat Kota Tomohon is 2233µg/Nm3, which generally, at most points and at certain times, still meets the air quality standards based on Government Regulation No. 22 of 2021. The highest CO level reached 2634µg/Nm3 at Location 1 in front of Anugerah Restaurant in the late afternoon to evening, which has high traffic density and charcoal burning activities. Meanwhile, from interviews with several satay vendors, information was obtained that they experience health complaints such as coughing, sore throat, shortness of breath, and chest pain. These complaints are strongly suspected to be related to exposure to charcoal burning smoke and vehicle emissions that occur regularly. This study concludes that although the CO concentration is generally still below the threshold, chronic exposure still has the potential to cause health problems for vulnerable populations such as satay vendors.